Preparation method of noble metal doped ultrathin hydroxide nano-cluster type electro-catalytic material
By preparing precious metal doped ultra -thin hydrogen oxide nano -clustered electrocatalyst materials on the foam nickel matrix, it solves the problem of high cost and complicated preparation of existing electrocatalyst materials, and achieves high -efficiency electrocatalytic performance and simplified preparation process. Essence
Patent Information
- Application Number
- CN202411498708.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
The existing electrocatalytic materials are costly, complex and environmentally friendly, and are difficult to effectively apply in the preparation of hydrogen energy electrolytic water.
The preparation method of the precious metal doped ultra -thin hydrogen oxide nano -cluster electrocatalyst material is used to prepare the nano cluster structure on the foam nickel matrix through the water heat reaction, and mix the valuable metal to simplify the process and reduce the cost.
The efficient electrical catalytic performance has been achieved, the reaction energy base is reduced, the hydrogen analysis response rate is improved, and the preparation process is simplified, the production cost is reduced, and it has good stability and adaptability.
Smart Images

Figure CN119372702A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a noble metal doped hydroxide electrocatalytic material, belonging to the technical field of electrocatalytic materials. Background Art
[0002] As the continuous use of traditional fossil fuels has brought about environmental pollution problems, there is an urgent need for a cleaner, more environmentally friendly and renewable fuel to solve the current dilemma. Hydrogen energy has received widespread attention as a clean energy with broad prospects. At present, electrolysis of water to produce hydrogen is one of the main methods for obtaining hydrogen energy. In the process of electrolysis of water, since the oxygen evolution reaction and the hydrogen evolution reaction require a large overpotential, electrocatalytic materials are usually used to accelerate the speed of the electrode reaction and improve the reaction efficiency. At present, Pt-based catalysts can significantly reduce the activation energy of chemical reactions and increase the reaction rate. However, since Pt is rare and expensive, its reserves are relatively limited, it is easy to deactivate in an acidic environment, and its stability is poor, which limits its wide application. Therefore, people are committed to developing a series of non-precious metal electrocatalysts represented by transition metals such as Fe-based, Co-based, and Ni-based. For example, the Chinese patent with publication number CN118256931A discloses the preparation of a composite electrocatalytic material, which is based on nickel foam (NF) and composited with multiple transition metal sulfides thereon. The preparation process is cumbersome, and toxic sulfides will be produced during the preparation process. In addition, a Chinese patent with publication number CN117107278A discloses the preparation of a Ni, Pt bimetallic MOF electrocatalytic material. The preparation method requires many types of raw materials and the preparation process is complicated and cumbersome, which is not conducive to industrialization.
[0003] According to existing literature reports, current electrocatalytic materials have the following main defects:
[0004] 1. Precious metal-based electrocatalysts are expensive, have poor durability, and are easily poisoned and deactivated;
[0005] 2. The preparation process of transition metal sulfides will produce toxic compounds, which is not conducive to the needs of green development;
[0006] 3. The preparation process of MOF-based materials is cumbersome, the production cycle is long, and the required equipment and preparation environment are demanding; Summary of the invention
[0007] The present invention aims to solve the technical problems of high cost, complex preparation process and environmental pollution of current electrocatalytic materials, and provides a method for preparing ultra-thin hydroxide nanocluster type electrocatalytic materials doped with precious metals. The method uses nickel foam as a substrate and prepares electrocatalytic materials for electrolyzing water to produce hydrogen with good electrocatalytic performance through simple process and low cost.
[0008] The method for preparing the precious metal-doped ultra-thin hydroxide nanocluster type electrocatalytic material of the present invention is carried out according to the following steps:
[0009] 1. Ultrasonic treatment of nickel foam in the form of sheet with solution I for 5 to 30 minutes, followed by drying to obtain nickel foam with a smooth surface;
[0010] 2. Weighing persulfate and transition metal salt in a molar ratio of persulfate to transition metal salt of 1:(50-100) and dissolving them in deionized water to obtain a mixed solution; wherein the transition metal salt is acetate, hydrochloride or nitrate of Cu, Co or Ni;
[0011] 3. Transfer the mixed solution to a reactor, add the nickel foam treated in step 1 to the reactor, place the reactor in an oven at 80-150° C. for 6-15 hours for hydrothermal reaction, close the oven after the reaction is completed, wait for it to gradually cool to room temperature, take out the nickel foam, wash it with deionized water, and dry it to obtain an intermediate;
[0012] 4. Dissolve the metal salt in solvent II to obtain a metal salt solution; the metal salt is ruthenium chloride, palladium chloride or rhodium chloride; transfer the metal salt solution to a reactor, add the intermediate into the reactor, place the reactor in an oven at 60 to 100°C for 6 to 15 hours for hydrothermal reaction, close the oven after the reaction is completed, wait for it to gradually cool to room temperature, take out the nickel foam, clean it with deionized water and ethanol respectively, and dry it to obtain a precious metal-doped ultrathin hydroxide nanocluster type electrocatalytic material.
[0013] Furthermore, the solution I in step 1 is one or a combination of any two of acetone, ethanol, hydrochloric acid and water;
[0014] Furthermore, the drying described in step 1 is carried out in an oven at a temperature of 50-60° C. for 60 minutes.
[0015] Furthermore, the persulfate in step 2 is a mixture of one or more of ammonium persulfate, sodium persulfate or potassium persulfate;
[0016] Furthermore, the concentration of the transition metal salt in the mixed solution in step 2 is 0.1 to 1 mol L – 1 ;
[0017] Furthermore, the drying described in step three is drying in an oven at a temperature of 60-80° C. for 60 minutes.
[0018] Furthermore, the solution II in step 4 is one or a combination of any two of acetone, ethanol, ethyl acetate and deionized water;
[0019] Furthermore, the concentration of the metal salt in the metal salt solution in step 4 is 1 to 10 mmol L – 1 ;
[0020] Furthermore, the drying described in step 4 is carried out in an oven at a temperature of 60-80° C. for 60 minutes.
[0021] The present invention first prepares a metal hydroxide with an ultrathin nanocluster structure on a nickel foam substrate through a hydrothermal reaction. The structure has a high specific surface area and is conducive to charge transfer. After being doped with a noble metal, the metals have a strong electronic interaction, so that the material has an excellent electron transfer rate and fast reaction kinetics, which can effectively reduce the reaction energy barrier and improve the hydrogen evolution reaction rate. The noble metal atoms are isolated and distributed on the surface of the metal hydroxide. The energy of the valence band electrons in the noble metal single atom (M-SAs) is extremely high, the electrons have a quantum confinement effect, and the atomic quantum energy level is sparse. These factors cause the metal single atom to have a very large surface free energy, and have a strong interaction with the carrier and the substance adsorbed on its surface. Therefore, the metal single atom material exhibits novel physical and chemical properties. In addition, the surface of the metal hydroxide has a high hydrophilicity, and the interface effect enhances the adsorption capacity of the reactant, thereby reducing the activation energy of the reaction. At the same time, the noble metal can increase the reaction rate, and the interaction between the two significantly improves the kinetics of the reaction.
[0022] The noble metal-doped ultrathin hydroxide nanocluster electrocatalyst material of the present invention is used as a working electrode in a 1M KOH solution at 10 mA cm – 2 The overpotential is 68~98mV, and the Tafel slope is as low as 96.8~112.3mV dec – 1 .
[0023] In addition, the electrocatalytic material prepared by the method used in the present application has a certain universality. According to different reactions or environmental conditions, by adjusting the types of precious metals and metal hydroxides used to prepare the electrocatalytic material, the structure and performance of the electrocatalytic material can be designed and optimized as needed to make it have better adaptability. The prepared intermediates can be combined with a variety of precious metals to form composite materials, thereby improving the electrocatalytic performance and broadening the scope of application.
[0024] The preparation method of the precious metal doped ultrathin hydroxide nanocluster type electrocatalytic material of the present invention is simple and easy to operate, does not require high-end technology or expensive process equipment, has low production cost, is easy to industrialize, and the prepared electrocatalytic material has good stability and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 X-ray diffraction spectra of Ni(OH)2 / NF prepared in step 3 and Ru-Ni(OH)2 / NF prepared in step 4 of Example 1. The horizontal axis is 2 times the diffraction angle, and the vertical axis is the relative intensity;
[0026] Figure 2 The scanning electron microscope images of Ni(OH)2 / NF prepared in step 3 of Example 1 and Ru-Ni(OH)2 / NF prepared in step 4, where a is Ni(OH)2 / NF and b is Ru-Ni(OH)2 / NF, and the scale is 2 um;
[0027] Figure 3 The linear sweep voltammetric curves of Ni(OH)2 / NF prepared in step 3 of Example 1 and Ru-Ni(OH)2 / NF prepared in step 4, the abscissa is the potential and the ordinate is the current density;
[0028] Figure 4 This is the Tafel slope diagram of the Ni(OH)2 / NF prepared in step 3 of Example 1 and the Ru-Ni(OH)2 / NF prepared in step 4, where the abscissa is the logarithm of the current density and the ordinate is the potential. DETAILED DESCRIPTION
[0029] The beneficial effects of the present invention are verified by combining the following specific examples:
[0030] Example 1: The preparation method of the noble metal-doped ultra-thin hydroxide nanocluster type electrocatalytic material of this example is carried out according to the following steps:
[0031] 1. A 3.5 cm × 4 cm sheet of nickel foam was cleaned with 1M HCl ultrasonically for 30 min, and then placed in an oven at 80°C for 1 h to obtain a nickel foam with a smooth surface;
[0032] 2. Weigh 1.16 g of nickel nitrate and 20 mg of potassium persulfate respectively, dissolve them in 35 mL of deionized water, and stir at room temperature for 10 min until they are completely dissolved to obtain a mixed solution;
[0033] 3. Transfer the mixed solution to a 50 mL hydrothermal reactor, add the nickel foam treated in step 1 to the hydrothermal reactor, and then place the hydrothermal reactor in an oven at 5 °C min. -1 The temperature was raised to 150°C and maintained for 10 hours for hydrothermal reaction. After the reaction was completed, the oven was closed and gradually cooled to room temperature. The nickel foam was taken out and washed with deionized water for 3 times. The nickel foam was then placed in an oven at 60°C and dried for 1 hour to obtain an intermediate, which was represented by Ni(OH)2 / NF.
[0034] 4. Dissolve 10 mg of ruthenium trichloride in 35 mL of ethanol to obtain a metal salt solution; then transfer the metal salt solution to a hydrothermal reactor, add the intermediate into the hydrothermal reactor, and then place the hydrothermal reactor in an oven at 80°C for 12 hours for hydrothermal reaction. After the reaction is completed, close the oven, wait for it to gradually cool to room temperature, take out the nickel foam, wash it with deionized water and ethanol three times respectively, and then put it in an oven at 60°C to dry for 1 hour to obtain a precious metal-doped ultrathin hydroxide nanocluster type electrocatalytic material, represented by Ru-Ni(OH)2 / NF.
[0035] The Ni(OH)2 / NF prepared in step 3 of Example 1 and the Ru-Ni(OH)2 / NF prepared in step 4 were subjected to X-ray detection, and the obtained XRD spectra were as follows: Figure 1 As shown, from Figure 1 It can be seen that after doping ruthenium chloride into Ni(OH)2, the crystal structure of the material did not change significantly.
[0036] The Ni(OH)2 / NF prepared in step 3 of Example 1 and the Ru-Ni(OH)2 / NF prepared in step 4 were subjected to scanning electron microscopy (SEM) testing. The obtained SEM photos are as follows: Figure 2 As shown, from Figure 2 It can be seen that the material is in the form of nanoclusters on the nickel mesh, and the thickness of the nanosheet is about 50nm.
[0037] The electrochemical performance of Ni(OH)2 / NF prepared in step 3 and Ru-Ni(OH)2 / NF prepared in step 4 was tested using a CHI660E electrochemical workstation. In a 1M KOH aqueous solution, a standard three-electrode system was used, with Ni(OH)2 / NF prepared in step 3 and Ru-Ni(OH)2 / NF prepared in step 4 as working electrodes, carbon rods as counter electrodes, and Hg / HgO as reference electrodes. The HER test voltage range was -1.5 to -0.8 V (vs. Hg / HgO), and the scan rate was 5 mV s -1 . According to the test results, the polarization curve is drawn as follows Figure 3 As shown, from Figure 3 It can be seen that in 1M KOH solution, at 10 mA cm –2 Under the condition of , the overpotential of Ni(OH)2 / NF prepared in step 3 is 214mV, and the overpotential of Ru-Ni(OH)2 / NF prepared in step 4 is as low as 68mV. Figure 4 As shown, from Figure 4 It can be seen that the Tafel slope is from 144.7mV dec – 1 Reduced to 96.8mVdec –1 . Comparison shows that after doping with the precious metal ruthenium, the metal ruthenium has a strong electronic interaction, which makes the material have excellent electron transfer rate and fast reaction kinetics, which can effectively reduce the reaction energy barrier and increase the hydrogen evolution reaction rate.
[0038] Example 2: This example is different from Example 1 in that 10 mg of ruthenium trichloride in step 4 is replaced by 10 mg of palladium dichloride, and the other steps and parameters are the same as those in Example 1. The obtained precious metal-doped ultrathin hydroxide nanocluster type electrocatalytic material is recorded as Pd-Ni(OH)2 / NF.
[0039] The electrochemical performance of the noble metal-doped ultrathin hydroxide nanocluster electrocatalyst prepared in Example 2 was tested in the same manner as in Example 1. In 1M KOH solution, Pd-Ni(OH)2 / NF was tested at 10 mA·cm –2 The overpotential is as low as 76mV and the Tafel slope is 98.5mV dec – 1 .
[0040] Example 3: This example is different from Example 1 in that 10 mg of ruthenium trichloride in step 4 is replaced by 10 mg of rhodium trichloride, and the other steps and parameters are the same as those in Example 1. The obtained precious metal-doped ultrathin hydroxide nanocluster type electrocatalytic material is represented by Rh-Ni(OH)2 / NF.
[0041] The electrochemical performance of the noble metal-doped ultrathin hydroxide nanocluster electrocatalyst prepared in Example 3 was tested by the same method as in Example 1. In 1 M KOH solution, Rh-Ni(OH)2 / NF was –2 The overpotential is as low as 89mV and the Tafel slope is 99.3mV dec – 1 .
[0042] Example 4: This example is different from Example 1 in that 1.16 g of nickel nitrate in step 2 is replaced by 0.75 g of copper nitrate, and the other steps and parameters are the same as those in Example 1. The obtained precious metal-doped ultrathin hydroxide nanocluster type electrocatalytic material is represented by Ru-Cu(OH)2 / NF.
[0043] The electrochemical performance of the noble metal-doped ultrathin hydroxide nanocluster electrocatalyst prepared in Example 4 was tested by the same method as in Example 1. In 1 M KOH solution, Ru-Cu(OH)2 / NF was –2 The overpotential is as low as 98 mV, and the Tafel slope of Ru-Cu(OH)2 / NF is 108.3 mV dec.–1 .
[0044] Example 5: This example is different from Example 1 in that 1.16 g of nickel nitrate in step 2 is replaced by 0.75 g of copper nitrate, and 10 mg of ruthenium trichloride in step 4 is replaced by 10 mg of palladium dichloride. The other steps and parameters are the same as those in Example 1. The obtained precious metal-doped ultrathin hydroxide nanocluster type electrocatalytic material is represented by Pd-Cu(OH)2 / NF.
[0045] The electrochemical performance of the noble metal-doped ultrathin hydroxide nanocluster electrocatalyst prepared in Example 5 was tested by the same method as in Example 1. In 1 M KOH solution, Pd-Cu(OH)2 / NF was –2 The overpotential is as low as 93mV and the Tafel slope is 112.3mV dec – 1 .
[0046] Example 6: This example is different from Example 1 in that 1.16 g of nickel nitrate in step 2 is replaced by 0.75 g of copper nitrate, and 10 mg of ruthenium trichloride in step 4 is replaced by 10 mg of rhodium trichloride. The other steps and parameters are the same as those in Example 1. The obtained precious metal-doped ultrathin hydroxide nanocluster type electrocatalytic material is represented by Rh-Cu(OH)2 / NF.
[0047] The electrochemical performance of the noble metal-doped ultrathin hydroxide nanocluster electrocatalyst prepared in Example 6 was tested by the same method as in Example 1. In 1 M KOH solution, Rh-Cu(OH)2 / NF was –2 The overpotential is as low as 90mV and the Tafel slope is 110.8mV dec – 1 .
[0048] Example 7: This example is different from Example 1 in that 1.16 g of nickel nitrate in step 2 is replaced by 1.16 g of cobalt nitrate, and the other steps and parameters are the same as those in Example 1. The obtained precious metal-doped ultrathin hydroxide nanocluster type electrocatalytic material is represented by Ru-Co(OH)2 / NF.
[0049] The electrochemical performance of the noble metal-doped ultrathin hydroxide nanocluster electrocatalyst prepared in Example 7 was tested by the same method as in Example 1. In 1 M KOH solution, Ru-Co(OH)2 / NF was –2 The overpotential is as low as 85mV and the Tafel slope is 103.6mV dec – 1 .
[0050] Example 8: This example differs from Example 1 in that 1.16 g of nickel nitrate in step 2 is replaced by 1.16 g of cobalt nitrate, and 10 mg of ruthenium trichloride in step 4 is replaced by 10 mg of palladium dichloride. The other steps and parameters are the same as those in Example 1. The obtained precious metal-doped ultrathin hydroxide nanocluster type electrocatalytic material is represented by Pd-Co(OH)2 / NF.
[0051] The electrochemical performance of the noble metal-doped ultrathin hydroxide nanocluster electrocatalyst prepared in Example 8 was tested by the same method as in Example 1. In 1 M KOH solution, Pd-Co(OH)2 / NF was –2 The overpotential is as low as 100mV and the Tafel slope is 105.8mV dec. – 1 .
[0052] Example 9: This example differs from Example 1 in that 1.16 g of nickel nitrate in step 2 is replaced by 1.16 g of cobalt nitrate, and 10 mg of ruthenium trichloride in step 4 is replaced by 10 mg of rhodium trichloride. The other steps and parameters are the same as those in Example 1. The obtained precious metal-doped ultrathin hydroxide nanocluster type electrocatalytic material is represented by Rh-Co(OH)2 / NF.
[0053] The electrochemical performance of the noble metal-doped ultrathin hydroxide nanocluster electrocatalyst prepared in Example 9 was tested by the same method as in Example 1. In 1 M KOH solution, Rh-Co(OH)2 / NF was –2 The overpotential is as low as 88mV and the Tafel slope is 105.8mV dec – 1 .
Claims
1. A method for preparing a noble metal-doped ultrathin hydroxide nanocluster type electrocatalytic material, characterized in that The method proceeds as follows:
1. Ultrasonic treatment of nickel foam in the form of sheet with solution I for 5 to 30 minutes, followed by drying to obtain nickel foam with a smooth surface; 2. Weighing persulfate and transition metal salt in a molar ratio of persulfate to transition metal salt of 1:(50-100) and dissolving them in deionized water to obtain a mixed solution; wherein the transition metal salt is acetate, hydrochloride or nitrate of Cu, Co or Ni; 3. Transfer the mixed solution to a reactor, add the nickel foam treated in step 1 to the reactor, place the reactor in an oven at 80-150° C. for 6-15 hours for hydrothermal reaction, close the oven after the reaction is completed, wait for it to gradually cool to room temperature, take out the nickel foam, wash it with deionized water, and dry it to obtain an intermediate; 4. Dissolve the metal salt in solvent II to obtain a metal salt solution; the metal salt is ruthenium chloride, palladium chloride or rhodium chloride; transfer the metal salt solution to a reactor, add the intermediate into the reactor, place the reactor in an oven at 60 to 100°C for 6 to 15 hours for hydrothermal reaction, close the oven after the reaction is completed, wait for it to gradually cool to room temperature, take out the nickel foam, clean it with deionized water and ethanol respectively, and dry it to obtain a precious metal-doped ultrathin hydroxide nanocluster type electrocatalytic material.
2. The method for preparing a noble metal-doped ultrathin hydroxide nanocluster type electrocatalytic material according to claim 1, characterized in that: The solution I described in step 1 is one or a combination of any two of acetone, ethanol, hydrochloric acid and water.
3. The method for preparing a noble metal-doped ultrathin hydroxide nanocluster type electrocatalytic material according to claim 1 or 2, characterized in that: The drying described in step 1 is carried out in an oven at a temperature of 50 to 60° C. for 40 to 60 minutes.
4. The method for preparing a noble metal-doped ultrathin hydroxide nanocluster type electrocatalytic material according to claim 1 or 2, characterized in that: The persulfate described in step 2 is a mixture of one or more of ammonium persulfate, sodium persulfate or potassium persulfate.
5. The method for preparing a noble metal-doped ultrathin hydroxide nanocluster type electrocatalytic material according to claim 1 or 2, characterized in that: The concentration of the transition metal salt in the mixed solution in step 2 is 0.1 to 1 mol L –1 .
6. The method for preparing a noble metal-doped ultrathin hydroxide nanocluster type electrocatalytic material according to claim 1 or 2, characterized in that: The drying described in step 3 is drying in an oven at a temperature of 60 to 80° C. for 40 to 60 minutes.
7. The method for preparing a noble metal-doped ultrathin hydroxide nanocluster type electrocatalytic material according to claim 1 or 2, characterized in that: The solution II described in step 4 is one or a combination of any two of acetone, ethanol, ethyl acetate and deionized water.
8. The method for preparing a noble metal-doped ultrathin hydroxide nanocluster type electrocatalytic material according to claim 1 or 2, characterized in that: The concentration of the metal salt in the metal salt solution in step 4 is 1 to 10 mmol L –1 .
9. The method for preparing a noble metal-doped ultrathin hydroxide nanocluster type electrocatalytic material according to claim 1 or 2, characterized in that: The drying described in step 4 is to dry in an oven at a temperature of 60-80° C. for 60 minutes.
Citation Information
Patent Citations
Preparation method of Ni-Pt bimetallic MOF electrocatalyst applied to preparation of ammonia gas through nitrogen reduction
CN117107278A
Co9S8 / Ni3S2 / Ni composite material and preparation method and application thereof
CN118256931A
Cited By
Electrocatalytic material, preparation method and application of electrocatalytic material in electrooxidation of urea
CN119912030A
Electrocatalytic material, preparation method and application thereof in electrooxidation of urea
CN119912030B